TOOLS AND METHODS OF LOW-FREQUENCY RADIO RECOMBINATION LINES INVESTIGATIONS - Konovalenko, A. A.; Stepkin, S. V.; Mukha, D. V.; Vasilkovskiy, E. V. (Одеські астрономічні публікації, 2016)
In the report the tools and methods of observations of radio recombination lines which are carried out atInstituteofRadio Astronomyof theNationalAcademy of Sciences ofUkraineusing the world’s largest decameter radio telescope UTR-2 (arrays “South – North” and “East – West”) are described. The low-frequency radio recombination lines can be used as effective means of the low-density partially ionized interstellar medium diagnostic. However, low intensities of the lines and high level of interferences makes such investigations very difficult and impose high requirements to equipment. Observations are carried out with the 4096-channel digital correlometer and new generation digital spectral processors with 8192 spectral channels. Currently, the systematic observations of radio recombination lines have been carried out in the directions of remnants of supernova stars, Galactic plane, nebulas and dust clouds. Experiments aimed to finding the redshifted line of neutral hydrogen HI which arises in the cosmological epochs of reionization in the range 8 – 32 MHz are carried out. The carbon radio recombination lines have been detected in the direction of Cassiopeia A in the broad range of frequencies from 20 to 32 MHz. The carbon radio recombination line, corresponding to the transitions to atomic level with number of 1009 (these corresponds to the Bohr size of atom near0,1 mm) have been registered.